2015
DOI: 10.1021/acs.jpclett.5b00131
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Altered Protonation Studied by Photoelectron Spectroscopy and Reactive Dynamics Simulations

Abstract: The extent to which functional groups are protonated at aqueous interfaces as compared to bulk is deemed essential to several areas in chemistry and biology. The origin of such changes has been the source of intense debate. We use X-ray photoelectron spectroscopy and all-atom reactive molecular dynamics simulations as two independent methods to probe, at the molecular scale, both bulk and surface distributions of protonated species of cysteine in an aqueous solution. We show that the distribution of the cystei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 23 publications
10
14
0
Order By: Relevance
“…Stimulated by these findings and by the satisfactory results obtained in our previous theoretical investigations regarding motion and reactivity of cysteine in water, on TiO 2 , and on gold supports we have extended our studies to describe the behavior of cystine in close contact with a gold substrate. The appearance of this molecule in our molecular dynamics (MD) simulations is not new.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Stimulated by these findings and by the satisfactory results obtained in our previous theoretical investigations regarding motion and reactivity of cysteine in water, on TiO 2 , and on gold supports we have extended our studies to describe the behavior of cystine in close contact with a gold substrate. The appearance of this molecule in our molecular dynamics (MD) simulations is not new.…”
Section: Introductionsupporting
confidence: 58%
“…The computational procedure we have used for studying adsorption modes and behavior in solution of the cysteine dimer was already employed successfully in the case of the monomer . The reactive force field parameters were carefully determined in an earlier work by choosing appropriate descriptors to render the interaction of the molecule with the metal support.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Apreviousstudy [24] has suggested that species at the surface of al iquid jet might differ from those observed in the bulk because of the surface effect. In our study on glycine nanoparti- Table 1.…”
mentioning
confidence: 99%
“…Suitable reactive force field (FF) parameters were identified through the optimization procedure included in the original program (serial ReaxFF), starting from the conjunction of the protein FF , and force fields developed by van Duin and co-workers for gold. These data were combined with other quantum chemistry (QC) data describing the interaction of the different atom types with Au (see Supporting Information).…”
mentioning
confidence: 99%